SPECTRAL AND PHOTOMETRIC STUDY OF TWO OBJECTS IRAS 22023+5249 AND IRAS 06053+1837 - Kondratyeva, L.N.; Denissyuk, E.K.; Reva, I.V.; Krugov, M.A.; Aimanova, G.K.; Omar, B.K.; Urmashev, B.A.; Mailybayev, A.T. (Academic Scientific Journal of Computer Science, 2020)
The objects IRAS 06053+1837 and IRAS 22023+5249, are considered as planetary nebula candidates. They have far infrared colors, which are typical to planetary nebulae. Their rather cool stars are surronded by envelopes, in which some low-excitation emission lines are formed. BV photometry of the object IRAS 22023+5249, carried out in 2017-2020, resulted the scatter of B and V values within 0m.25 and 0 m.10 respectively. Moreover a tendency of the gradual increasing of brightness is revealed. Absolute fluxes and equivalent widths of the Hβ, Hα, [NII], 6548, 6583A and HeI, 6678A emission lines in the spectrum of IRAS 22023+5249 are determined. The strengthening of the emission lines is confirmed. Most likely increasing of an effective temperrature of the star is responsible for observable variations. As a whole spectral and photometric characteristics of the object IRAS 22023+5249 correspond to its status as a low-excitation planetary nebula. For the object IRAS 06053+1837observable data are obtained in 2014 -2019. Much larger the scatter of B V R values is observed: 0m.50, 0m.15 and 0 m.30 respectively. The only HI emission lines are presented in its spectrum. Asymmetrical profiles of lines have broad wings on the short wavelength side. The evolutionary status of the object is not defined; its characteristics, are more similar to those of the young AeBe Herbig stars.